Southwest Research-Extension Center Field Day 2006 Forage research supplement (Kansas Agricultural Experiment Station Research Reports, 2006)
This publication is a supplement to Field Day 2006, Southwest Research-Extension Center Report of Progress SRP 961 from the Kansas Agricultural Experiment Station.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 961-S; Kansas Agricultural Experiment Station contribution; no. 07-34-S; Kansas; Hard red winter wheat; Hard white winter wheat; Cool-season grass; Warm-season grass; Corn harvest residue; Yield